Aktivitas Antijamur Fraksi n-Heksana, Etil Asetat, dan Air dari Ekstrak Metanolik Daun Bunga Pukul Empat (Mirabilis jalapa L.) terhadap Pityrosporum ovale ATCCÂ® 3179 - Agnes Christina Budiwati; Gunawan Pamudji Widodo; Iswandi Iswandi (Jurnal Farmasi Indonesia, 2014)
Leaves of Mirabilis jalapa L. can inhibit the growth of Staphylococcus aureus and Aspergillus sp. The study aimed to determine the antifungal activity of n-hexane, ethyl acetate, and water fractions from the methanolic extract of leaves of Mirabilis jalapa L. against Pityrosporum ovale fungi and to determine the most effective fraction in inhibiting the growth of Pityrosporum ovale. Antifungal activity assays using the diffusion method, in which the test solution of Mirabilis jalapa L. leaves made serial consentrations of 10%, 5%, 3% entered in wells that have been applied to SGA media fungal suspension test. The results was analyzed using two ways statistical analysis. The result showed that of n-hexane, ethyl acetate, and water fractions from methanolic extracts Mirabilis jalapa L. leaves have antifungal activity against Phytyrosporum ovale. Ethyl acetate fraction at a concentration of 10% had the highest antifungal activity was 25 mm.